Irradiation as a postharvest treatment of cavendish banana (Musa sapiendum var Cavendish) - Medianesta, Rhona Cabuyao (2002)
ABSTRACT The rapid ripening of Cavendish bananas after ethylene treatment and the incidence of crown rot are two of the major areas of concern for this export cultivar. The use of gamma radiation in extending shelf life of fruits and vegetables, without posing hazards of chemical residues, has shown promise and was therefore considered for Cavendish bananas. This study aimed at the determination of the efficacy of irradiation in extending shelf life of ethylene-treated bananas. Various radiation doses were used to treat Cavendish bananas at two distinct degrees of ripeness, subsequently stored at different storage temperatures. Phase I involved irradiation of Cavendish bananas at peel color 3 using 0.1, 0.3, 0.5 and 1.0 kGy doses and quality assessment during storage at 21-25°C. Phase II dealt with irradiation of Cavendish bananas at peel color 2 using the optimum doses determined in Phase I, which were 0.3 and 0.5 kGy. Quality evaluation was performed at peel colors 5, 6, and 7 of the samples during storage at 16-20°C. The effect of temperature break was also considered in this phase. In Phase I, ANOVA at α = 0.05 indicated no significant difference between control and irradiated Cavendish bananas in terms of pH, peel-to-pulp ratio and sensory attributes of the fruit. At 1.0 kGy, the fruits were softer and have lower °Brix values than the other lots. Incidences of spoilage and crown rot were inhibited at doses 0.3, 0.5 and 1.0 kGy. Doses of 0.3 and 0.5 kGy were found to be the optimum doses possible for shelf life extension of the Cavendish bananas. In Phase II, observations made on the four lots of Cavendish bananas (+ control, - control, 0.3 kGy radiation dose treatments) showed that no significant differences existed among treatments in terms of pH, total soluble solids, firmness, peel-to-pulp ratio and sensory attributes of the samples. Incidence of crown rot was considerably lower in the irradiated than in the control bananas. Ripening was delayed by 1 and 2 days in 0.3 and 0.5 kGy-treated samples, respectively. The length of storage may be extended by a day provided there is no interruption in the holding temperature of the fruit, which is 15°C. In terms of the degree of ripeness and storage temperature, irradiation at peel color 2 and storage at 16-20°C were found to extend shelf life of ripened Cavendish bananas by a day more than in the irradiated fruit at peel color 3 with subsequent storage at 21-25°C using 0.3 and 0.5 kGy radiation d